Oriented PrBaCo2O5+δ thin films for solid oxide fuel cells - Gao, Y.; Chen, D.; Chen, C.; Shao, Zongping; Ciucci, F. (Elsevier, 2015)
Oriented PrBaCo2O5+δ (PBC) thin films are prepared on yttria-stabilized ZrO2 (YSZ) substrates with orientations (001), (110) and (111) via pulsed laser deposition (PLD). Electrochemical impedance spectroscopy (EIS) experiments at various temperatures and oxygen partial pressures reveal a good oxygen reduction reaction (ORR) performance of all the thin films. However, the films' performance has considerable variance. PBC thin film deposited on (111) oriented YSZ had the best performance, followed by (110) and (001). Experiments including high resolution X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), and computation, namely molecular dynamics (MD), are used to elucidate the substrate-determined orientations, examine the morphology and composition of the thin films, and to explain the variance of the ORR performance. Our results support the anisotropy of the oxygen vacancy pathway in the a–b plane and indicate that the substrate orientations can have great influence on the thin films properties.